Shakespeare's moral compass - Parvini, Neema (Edinburgh critical studies in Shakespeare and philosophy., 2018)
This book combines research in evolutionary psychology, historical scholarship, and philosophy to answer a question that has eluded critics for centuries: what is Shakespeare's moral vision?